The Role of Robotic Surgery in the Management of Hiatal Hernias - Adem AKÇAKAYA (Bezmiâlem Science)
Robotic surgery (RS) has recently become an increasingly preferred minimally invasive approach for hiatal hernia repair. This commentary discusses the efficacy of RS compared to laparoscopic surgery (LS) in light of current meta-analyses and retrospective studies. RS offers technical advantages such as three-dimensional visualization, enhanced dexterity, and improved ergonomics, potentially providing superior precision for surgeons. Several studies have reported lower postoperative complication rates and, in some cases, shorter hospital stays in the RS group. However, operative times did not show a statistically significant difference between the two techniques. Large-scale meta-analyses indicated no clear clinical superiority of RS over LS, while costs associated with RS were significantly higher. Additionally, the retrospective nature of most studies and the heterogeneity in patient characteristics limit the generalizability of the findings. Despite its promising technical capabilities and increasing surgeon experience, further randomized controlled trials are necessary to establish the clinical benefits of RS. Nevertheless, RS represents a promising approach that may become more widely adopted in hiatal hernia surgery in the near future.